1965
DOI: 10.1002/nav.3800120303
|View full text |Cite
|
Sign up to set email alerts
|

The kernel of a cooperative game

Abstract: M o r t o n D a v i s T h e C i t y U n i v e r s i t y of N e w Y o r k and M i c h a e l M a s c h l e r T h e H e b r e w U n i v e r s i t y J e r u s a l e m , I s r a e l ABST RAG T The kernel of a cooperative n -p e r s o n game i s defined. It i s a subs e t of the bargaining s e t m:i). Its existence and some of i t s p r o p e r t i e sa r e studied. We apply it to the 3-person games, to the 4-person constants u m games, to the s y m m e t r i c and n-quota g a m e s and to games in which only the n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
354
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(365 citation statements)
references
References 4 publications
5
354
0
6
Order By: Relevance
“…In this section we establish that the Aumann-Maschler and the lvlas-Colell bargaining sets of a continuous game with a countable set of players are non-empty sets which contain the intersection of the prekernel and the least coreo Davis and Maschler [4], and Peleg [14] showed that if v is a garne with a finite set of players, then B (v) is a non-ernpty seto For this class of garnes, Davis and Maschler [5] proved that K (v) …”
Section: Bargaining Setsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this section we establish that the Aumann-Maschler and the lvlas-Colell bargaining sets of a continuous game with a countable set of players are non-empty sets which contain the intersection of the prekernel and the least coreo Davis and Maschler [4], and Peleg [14] showed that if v is a garne with a finite set of players, then B (v) is a non-ernpty seto For this class of garnes, Davis and Maschler [5] proved that K (v) …”
Section: Bargaining Setsmentioning
confidence: 97%
“…The notion of the kernel of a eoalitional game with a finite set of players was introdueed by Davis and Masehler [5]. It is well-known that if v is a superadditive game with a finite set ofplayers, then…”
Section: The Least Eorementioning
confidence: 99%
See 1 more Smart Citation
“…In "Rationality, aggregate monotonicity and consistency in cooperative games: some (im)possibility results," Pedro Calleja and Francesc Llerena consider domains of cooperative games with transferable utility and investigate the existence of singlevalued solutions satisfying individual rationality, core selection, monotonicity, and consistency. They obtain impossibility results for the combination of core selection and complementary consistency (Moulin 1985), or project consistency (Funaki 1998), or monotonicity and max consistency (Davis and Maschler 1965). However, they derive possibility results for the combination of individual rationality, monotonicity, and project consistency.…”
Section: Exploring the Implications Of Consistencymentioning
confidence: 99%
“…The kernel, denoted here by K, was introduced by Davis and Maschler (1965). In this paper we only consider its intersection with the core.…”
Section: Preliminariesmentioning
confidence: 99%